The Influence of Servicescape on Travel Decisions with Customer Satisfaction as a Moderating Variable - Eva Desembrianita; Agus Sunatha Putra; Muhammad Fikri Maulana; Heppi Syofya; Julinta Paulina (Yayasan Inovasi Kemajuan Intelektual, 2025)
This quantitative study uses an explanatory approach emphasizing basic research to compile arguments systematically and according to applicable scientific rules. The data used in this study are primary data that researchers obtained from tourists to Java S Beach, Beaches in Bali, and Beaches in Lampung, totaling two hundred and eighty-five foreign and local tourists. The data obtained by researchers were analyzed using the smart PLS 4.0 analysis tool. The result in this article shows that all hypotheses in this study can be accepted and proven. In the first hypothesis, the Serviceescape variable can have a positive relationship direction and a significant influence on Travel/Visit Decisions at a tourist attraction because the P-values are positive and below the 0.05 significance level, namely 0.013. This indicates that better Serviceescape implementation at a tourist attraction can make tourists more comfortable and interested, and help them decide to visit. In the following hypothesis, the Customer Satisfaction variable can strengthen the influence of the Serviceescape variable on Visit Decisions. The P-values are positive and below the 0.05 significance level, 0.000. Thus, it can be concluded that this article's first and second hypotheses are acceptable.